PERAMALAN PRODUKSI TELUR UNTUK MENDUKUNG PROGRAM MAKAN BERGIZI DI LAMPUNG (Forecasting Egg Production to Support the Nutritious Meal Program in Lampung) - Febriati, Nurullia -; Hidayati, Sri (Jurnal Agroindustri Berkelanjutan, 2025)
Eggs are one of the animal-based food sources with high protein content, relatively affordable prices, and wide availability in the market. Their complete nutritional composition makes eggs an important source of animal protein to support national food security programs, including the implementation of free meal programs for communities and students. To ensure sustainable availability, a production forecasting analysis is required to anticipate future demand. This study aims to forecast egg production in Lampung Province, one of Indonesia’s key poultry-producing regions. Forecasting was conducted using three methods: Moving Average, Weighted Moving Average, and Exponential Smoothing. Secondary data were obtained from the Department of Animal Husbandry and the Central Bureau of Statistics (BPS) of Lampung Province, covering the period from 2018 to 2024. The analysis compared the accuracy of each method using the Mean Absolute Percentage Error (MAPE) criterion. The results of this study indicate that the Exponential Smoothing with Trend method, with a parameter α = 0.6, produced the most accurate forecast with the lowest MAPE value of 22.166%. This value suggests that the method provides a reasonably good estimation of the egg production trend in Lampung Province. The findings are expected to serve as a basis for decision-making and planning related to the supply of animal-based protein foods, particularly eggs, in support of government programs aimed at improving community nutrition and maintaining the stability of egg supply and prices in local markets.